Pengaruh Media (Powtoon) Terhadap Pembelajaran Teks Drama Siswa Kelas XI SMA Negeri 10 Makassar - Haslinda, Haslinda; Muh Reza Anugerah Putra; Muhammad Akhir (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
Indonesian Language Learning for Class XI IPA and XI IPS of SMA Negeri 10 Makassar is quite low due to the use of inappropriate learning media which results in students not understanding Indonesian Language learning, the role of learning media in the learning process is something that cannot be separated from the world of education. Isn't it true that with the existence of various learning media, students are able to have many choices of learning media that can be used in the learning process according to their personal characteristics. The purpose of this study was to describe the effect of Powtoon Media on the Drama Text Skills of students in class XI MIPA 1 and class XI IPS 1. This study used the Quasi Experimental Design research method. The population in this study were all students of class XI MIPA and IPS at SMA Negeri 10 Makassar. The sampling technique used was simple random sampling. The instruments used in this study were observation sheets and test instruments in the form of multiple choice questions to measure student learning outcomes with Pretest - Posttest Control group Design. The results of the study showed that the learning outcomes of students before being given treatment in learning Drama Texts for class XI MIPA 1 and XI IPS 1 obtained the same average value of 20. While the learning outcomes obtained after being given treatment obtained an average value of 19.53 (experimental class) with the help of powtoon media and 19.28 (control class) using power point media. Furthermore, the value obtained from the hypothesis test using the Independent Sample T Test. Sig. (2-tailed) of 0.000 <0.05 which means that there is a significant influence on student learning outcomes in learning Drama Texts